Translating urban tourist icons across cultures: an English-Malay perspective - Mohamed Zain Sulaiman (Penerbit UKM, 2014)
Urban tourist icons such as Paris, Istanbul or Sydney are major pull factors of a destination and are often represented in tourist promotional texts (TPTs) to persuade potential tourists to visit a destination. The use of the ‗iconic advertising approach‘(Litvin & Mouri, 2009), which capitalises on the iconicity of tourist icons, is one of the most effective advertising approaches in affecting a destination image. The strength of this approach lies in its key function of representing easily recognisable and positive images that reinforce or simply recall the audience‘s previously held perceptions about the destination. However, the ways in which urban tourist icons are represented and perceived differ from one audience to another, for it is based on the cultural background of the audience. The differences in how these icons are represented and perceived pose a key challenge for translators of TPTs, whose role is to produce an effective translation in the target language and culture in order to persuade potential tourists in that language and culture. This paper discusses some of the cultural issues involved in translating tourist icons and analyses how a particular ‗tourist icon‘ is represented in a published English TPT (source text) for an Anglo audience and how it has been translated into the Malay language for a Malay audience. The translation (target text) is analysed in terms of its functionality and effectiveness within the cultural context of the target audience. The discourse analysis of the source and target texts is complemented by findings derived from focus group discussions and an analysis of authentic TPTs in Malay (parallel texts). Based on the analysis, a functionally adequate translation which takes into consideration the cultural differences, hence preserving the iconicity of the destination, is proposed.